Empirical Study On The Usage And Effectiveness Of Digital Multimedia Elements In A Computer-Aided Learning Application - Shamsuar, Natalya Rudina (2007)
This thesis critically reviews the important characteristics of multimedia elements and combinations as a learning material conveyance tool. A exploratory observation is conducted to ascertain how multimedia and its elements are used to deliver a selected group of learning materials. The observation provides an insight on the usage of multimedia and serves as the basis to further develop the research.